Novel compact dual-broadband planar metamaterial antenna - Dinh, Dang Nhu; Liem, Dinh Thanh; Phuong, Huynh Nguyen Bao; Chi, Hoang Phuong; Chien, Dao Ngoc (Vietnam Journal of Science and Technology, 2017)
This paper proposes a novel uni-planar dual-band antenna using Composite Right Left Handed (CRLH) transmission line (CRLH-TL). Proposed antenna is designed based on the fringing effects of metamaterials and combined with coplanar waveguide (CPW) feeding in order to create two frequency bands for WLAN applications at the 2.4 and 5.5 GHz bands. Principle of gradual transform is applied to the antenna for extending the resonance frequency ranges. Optimized metamaterial antenna are fabricated and measured. Measurement results showed that the antenna operates in two broad frequency ranges spreading from 1.8 to 3.62 GHz and from 4.85 to 7.52 GHz with very compact overall dimensions of 18 mm × 16 mm (0,147 λ0 × 0.13λ0).